Vibration control and energy harvesting of adjacent structures by electromagnetic dampers considering soil-structure interaction - Xiaofang Kang; Zongqin Wu; Wei He; Xinqi Wang; Xueqin Jiang (Journal of Engineering and Applied Science)
Abstract With rapid urbanization, the increasing density of buildings in urban areas has forced us to consider interactions between adjacent structures. However, most studies have focused on fixed foundations, neglecting soil-structure interactions (SSI). This paper addresses this gap by investigating the optimization of two adjacent structures using electromagnetic inerter dampers (EMID) under SSI. The EMID system, equipped with energy harvesting capabilities, was optimized using the Monte Carlo search method, with results demonstrating a significant reduction in dynamic response. Specifically, frequency and time domain analyses show that the EMID system reduces peak displacement and acceleration by up to 41.23% compared to uncontrolled structures. Additionally, the system efficiently converts seismic energy into electrical energy, with energy harvesting reaching peak values under intense seismic waves, such as those observed in Mexico City earthquake conditions. This innovative system not only enhances seismic performance, particularly in soft soil conditions, but also offers energy resilience by supplying emergency power, thus highlighting its potential for sustainable urban infrastructure.